2020
DOI: 10.3390/plants9091124
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Pharmacological Study of the Eysenhardtia Genus

Abstract: The participation of natural products in health care has been remarkable, and today they continue to play a key role in the discovery and development of new treatments. Phytochemical studies together with pharmacological tests have managed to integrate bioactive agents as an alternative solution to reduce or regulate the problems caused by diseases. The Eysenhardtia genus is a family of plants that are rich in secondary metabolites, which have shown potential activity in the control and mitigation of urinary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In a study, we found that in extracts with a mixture of chloroform and methanol (1:1) of Cnidoscolus chayamansa cell suspension cultures, lupeol acetate was obtained (38.1 mg/g extract), and the extracts had antibacterial activity [ 41 ]. Nonanedioic acid, β -sitosterol, stigmasterol, stigmasta-3,5-dien-7-one, β -amyrin, ( Z,Z )-9,12-octadecadienoic acid, D-pinitol, hexadecanoic acid, and other compounds have been reported for Eysenhardtia genus and some Fabaceae species [ 10 , 11 , 42 ]; however, in this work, the phytochemical screening by GC‒MS analysis of plants and cell suspension culture extracts from E. platycarpa is reported for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, we found that in extracts with a mixture of chloroform and methanol (1:1) of Cnidoscolus chayamansa cell suspension cultures, lupeol acetate was obtained (38.1 mg/g extract), and the extracts had antibacterial activity [ 41 ]. Nonanedioic acid, β -sitosterol, stigmasterol, stigmasta-3,5-dien-7-one, β -amyrin, ( Z,Z )-9,12-octadecadienoic acid, D-pinitol, hexadecanoic acid, and other compounds have been reported for Eysenhardtia genus and some Fabaceae species [ 10 , 11 , 42 ]; however, in this work, the phytochemical screening by GC‒MS analysis of plants and cell suspension culture extracts from E. platycarpa is reported for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…All these uses, as well as forest fires, are causing a decline in wild populations. Among the few existing investigations on E. platycarpa , all of them have used the wild plant as a source of pharmacological studies [ 10 ]. For instance, flavonoids with cytotoxic and antibacterial activity were isolated from methanolic extracts of branches and leaves of E. platycarpa [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study, we found that in extracts with a mixture of chloroform and methanol (1:1) of Cnidoscolus chayamansa cell suspension cultures, lupeol acetate was obtained (38.1 mg/g extract), and the extracts had antibacterial activity [41]. Nonanedioic acid, β-sitosterol, stigmasterol, stigmasta-3,5-dien-7-one, β-amyrin, (Z,Z)-9,12-octadecadienoic acid, D-pinitol, hexadecanoic acid, and other compounds have been reported for Eysenhardtia genus and some Fabaceae species [10,11,42]; however, in this work, the phytochemical screening by GC-MS analysis of plants and cell suspension culture extracts from E. platycarpa is for the first time.…”
Section: Compounds Identified By Gc-msmentioning
confidence: 95%
“…All these uses, as well as forest fires, are causing a decline in wild populations. Among the few existing investigations on E. platycarpa, all of them have used the wild plant as a source of pharmacological studies [10]. For instance, flavonoids with cytotoxic and antibacterial activity were isolated from methanolic extracts of branches and leaves of E. platycarpa [11].…”
Section: Introductionmentioning
confidence: 99%
“…From this family of plants, many compounds have been isolated, such as flavones, isoflavones, flavanones, phenolic compounds, chalcones, dihydrochalcones, coumarins, pterocarpan, sugars, and fatty acids, among others. Several pharmacological studies have been linked to the identification of its health benefits, highlighting diuretic, antidiabetic, antiglycation, antioxidant, anti-inflammatory, antimicrobial potential, and cytotoxic properties [17]. Narvaez-Mastache et al demonstrated the antioxidant and anti-hyperglycemic activities of 3-O-Acetyl-11α,12α-epoxy-oleanan-28,13β-olide isolated from Eysenhardtia platycarpa, E. punctata, and E. subcoriacea (Fabaceae) species [18].…”
Section: Introductionmentioning
confidence: 99%